Wpływ Skręcania na Rozciąganie Pręta Pryzmatycznego o Dowolnym Kształcie Przekroju w Zakresie Sprężysto-Plastycznym - M. Wnuk (Engineering Transactions)
The problem under consideration is that of combined tension and torsion in the elastic-plastic range. The Hencky-Ilyushin plastic strain theory is used assuming a Prandtl body that is a perfectly plastic, incompressible body, Making use of the perturbation method an approximate solutionis obtained valid for large N and small Ms only (N – longitudinal force, Ms - torque). The equations found for the stress components, the loads and the frontier between the two regions I(x,y) = 0 are given in the form of power series. They are valid for any cross-section. Effective solution of the problem is obtained in four cases concerning a circle, an ellipse, a regular triangle, and an airfoil.